Computer organization and design : the hardware/software interface - Patterson, David A.; Hennessy, John L.; Hennessy, John L. (Waltham, MA : Morgan Kaufmann, 2012)
"Presents the fundamentals of hardware technologies, assembly language, computer arithmetic, pipelining, memory hierarchies and I/O"--
Machine generated contents note: Computer Abstractions and Technology Instructions: Language of the Computer Arithmetic for Computers Assessing and Understanding Performance The Processor Enhancing Performance with Pipelining Large and Fast: Exploiting Memory Hierarchy Storage, Networks and Other Peripherals Multiprocessors and Clusters Mapping Control to Hardware A Survey of RISC Architectures for Desktop, Server, and Embedded Computers.
Rev. ed. of: Computer organization and design / John L. Hennessy, David A. Patterson. 1998.
Includes index.
Keywords: Computer organization; Computer engineering; Computer interfaces